2015
DOI: 10.1177/0009922815590223
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Concept Mapping and Critical Thinking in Fourth-Year Medical Students

Abstract: A recent meta-analysis confirms this is the first report of a comparison between the increasingly common CCTST and the USMLE. We confirmed that concept mapping is a valid mechanism to teach content knowledge. Although the difference in the CCTST scores was not significant, this study could serve as an important start toward development of a curriculum devoted to teaching content and improving CT. The small number of students may have prevented us from defining a significant impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 24 publications
1
22
3
Order By: Relevance
“…Our findings were also inconsistent with Bixler et al () who found no significant increase in CT as measured by the CCTST and CCTDI from pretest to posttest when students were educated using a concept mapping approach. Bixler et al concluded that although the difference in CT scores was not significant, the study could serve as an important start toward the development of a curriculum devoted to improving CT.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings were also inconsistent with Bixler et al () who found no significant increase in CT as measured by the CCTST and CCTDI from pretest to posttest when students were educated using a concept mapping approach. Bixler et al concluded that although the difference in CT scores was not significant, the study could serve as an important start toward the development of a curriculum devoted to improving CT.…”
Section: Discussioncontrasting
confidence: 99%
“…They found that the results, while not statistically significant, were associated with a gain in knowledge and potential advantages of providing an active learning approach with the material. 13 Although no significant change in CCTST total scores was found, this study is an important starting point to improve understanding regarding the development of critical thinking and its skills in undergraduate nursing students in Brazil. The study involved a relatively short intervention and the results allow us ask important questions about the optimal duration of teaching activities with the aim of teaching content while improving critical thinking skills.…”
Section: Discussionmentioning
confidence: 69%
“…Professors need to carefully select topics for concept mapping and devote adequate time to this activity in order to increase perceived and real learning. 13 Thus, the evolution of students in the mentioned skills is understandable, the identification of signs and symptoms, assessment and decision making are encouraged at all times during ACLS education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is expected more than ever to prepare graduate nurses who are competent, knowledgeable, and skillful; subsequently safe and quality practice can be achieved [3]. Therefore, undergraduate nursing curricula and their related teaching and learning practices must be Issues related to autonomous professional nurses who are able to use reasoned judgment and critical thinking to support clinical decisions are extensively discussed in the literature [5], and hence, these skills are now expected outcomes of nursing undergraduate and graduate programs [6]. However, in order to guide the current nursing education, many educators are striving to explore alternative teaching strategies that promoting an effective meaningful learning rather than sticking with traditional lectures [7] [8].…”
Section: Introductionmentioning
confidence: 99%